11. \( \frac{\left(27 x^{9} y^{-3}\right)^{-\frac{2}{3}}}{\sqrt{9^{-1} x^{-8}} y^{2}} \)
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Extra Insights
To simplify the expression \( \frac{\left(27 x^{9} y^{-3}\right)^{-\frac{2}{3}}}{\sqrt{9^{-1} x^{-8}} y^{2}} \), we will first simplify the numerator and denominator separately. Starting with the numerator: 1. **Numerator**: \[ \left(27 x^{9} y^{-3}\right)^{-\frac{2}{3}} = \left(27^{-\frac{2}{3}} x^{-6} y^{2}\right) \] Since \( 27 = 3^3 \), we have: \[ 27^{-\frac{2}{3}} = (3^3)^{-\frac{2}{3}} = 3^{-2} = \frac{1}{9} \] So the numerator becomes: \[ \frac{1}{9} x^{-6} y^{2} \] 2. **Denominator**: \[ \sqrt{9^{-1} x^{-8}} y^{2} = \sqrt{\frac{1}{9} x^{-8}} y^{2} = \frac{1}{\sqrt{9}} \sqrt{x^{-8}} y^{2} = \frac{1}{3} x^{-4} y^{2} \] Now, the expression looks like this: \[ \frac{\frac{1}{9} x^{-6} y^{2}}{\frac{1}{3} x^{-4} y^{2}} \] When you divide fractions, you multiply by the reciprocal: \[ = \frac{1}{9} x^{-6} y^{2} \cdot \frac{3}{x^{-4} y^{2}} = \frac{1 \cdot 3}{9} \cdot \frac{x^{-6}}{x^{-4}} \cdot \frac{y^{2}}{y^{2}} = \frac{3}{9} x^{-2} = \frac{1}{3} x^{-2} \] Finally, we express \( x^{-2} \) in a more friendly form: \[ \frac{1}{3x^2} \] Thus, the simplification of the expression is: \[ \frac{1}{3x^2} \]